Current Scenario of Poisoning and Snake Bite Patients Admitted in Sylhet MAG Osmani Medical College Hospital - Saha, Mrinal; Mahamud, Sajjad; Rahul, Abu Kamran; Rahman, Mohammad Ferdous (Bangladesh Journal of Medicine, 2023)
Background: Poisoning cases are still neglected in our society. Recent studies have revealed the increasing trend of poisoning and snake bite patients, which may be a big challenge shortly. This study was carried out to observe the epidemiological profile of acute poisoning and snake bite in northeastern Bangladesh and to evaluate the risk factors, patterns and mortality. Methods: Data was collected from the emergency admission registrar of Sylhet MAG Osmani Medical College Hospital with a history of poisoning or snake bite from 1st January 2022 to 30th September 2022. Then indoor ward registers were used to see the outcomes. Results: 774 patients were admitted in the last nine months. Among them, 707 were poisoning cases (406 males and 301 females), and 67(48 males and 19 females) were snake bites. We found 201 (28%) patients with unknown poisoning, and 167 (24%) were OPC poisoning. Other poisoning types were drug overdose (sedative, paracetamol, antipsychotic, anti-depressant and anti-hypertensive) and corrosive poisoning (Herpic, Dettol, Savlon, Detergent, Soap, Household Cleaning Materials, and paraquat). Though less frequent (11 cases), parquet poisoning was the most fatal. Regarding, Snakebite, 16 (24%) were venomous, and 44 (66%) were non-venomous. At last, we observed 45 deaths (Poisoning 40 and Snakebite 5). Conclusion: Both poisoning and snake bite cases are important in the clinical context of every tertiary care hospital like ours. To reduce this burden, we should focus on the risk factors. At the same time, proper treatment guideline is necessary even in the rural setup to ensure initial life-saving care. Bangladesh J Medicine 2023; 34(2): 133-136